Strategi Komunikasi Interpersonal Premori Retail Dalam Meningkatkan Loyalitas Reseller Pada Komunitas “Be A Founder” - Erina Anggraeni; Yudiana Indriastuti (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
Reseller loyalty is a crucial factor in maintaining B2B business stability, especially in the competitive off-label premium hijab industry. However, studies on how interpersonal communication strategies can be effectively used to build reseller loyalty in the context of digital business communities are still limited. This research aims to analyze the interpersonal communication strategies applied by Premori Retail in building reseller engagement and loyalty in the “Be a Founder” community. This research uses a qualitative approach. With data collection techniques conducted through participatory observation and in-depth interviews with active resellers and the CEO of Premori Retail. The analytical framework refers to Joseph A. DeVito's interpersonal communication theory which includes five main indicators: openness, empathy, support, positive attitude, and equality. The results show that Premori Retail's interpersonal communication is flexible, responsive and personalized. This approach is able to adapt to the needs of individual resellers and create a sense of being valued and cared for. This strategy contributes significantly to building resellers' emotional loyalty to the company. The unique contribution of this research lies in the strategic mapping of interpersonal communication practices in the digital reseller community ecosystem, which has not been widely revealed in business communication studies in Indonesia.